Knowledge and Attitude on Refractive Errors among Students of a School in Dharan - Limbu, Lawati; Basnet, Saraswati (Journal of Research and Development, 2026)
Refractive error is a common eye disorder among school-age children and is the second leading cause of treatable blindness. Globally, more than two billion people are estimated to be visually impaired. Of these, twelve million children are visually impaired due to refractive errors. A lack of knowledge and an unfavorable attitude toward refractive error can lead to long-term consequences for children's well-being and academic performance. This study aimed to assess the knowledge and attitudes on refractive error among secondary-level students. A cross-sectional analytical study was conducted among 280 students of Dharan Adarsha Boarding Secondary School, Dharan. A non-probability purposive sampling method was used, and data were collected through a self administered structured questionnaire. The data were analyzed using SPSS version 16.0. Descriptive statistics (frequency, percentage, mean, and standard deviation) and inferential statistics (Chi-square test) were used for data analysis. The study revealed that 55.7% of respondents had a moderately adequate level of knowledge about refractive errors, while 53.2% exhibited a negative attitude toward refractive errors and their corrective measures. Statistically significant associations were found between knowledge levels and variables such as sex and family income per month. Similarly, significant associations were found between attitude levels and variables including age, grade, sex, and previous eye examination. The study concluded that nearly one-third of the students lacked adequate knowledge about refractive errors, and the majority exhibited negative attitudes towards it. This shows the need for school-based eye health awareness programs to improve knowledge, reduce stigma, and encourage early detection and treatment of refractive errors.